1986
DOI: 10.4141/cjps86-040
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Adventitious Roots and Agronomic Characteristics in Barley

Abstract: Hocrnrr, E. A. 1986. Relationship

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…These tillers produce nodal (adventitious) roots which penetrate easily in soil along with seminal roots and establish a network of extensive roots by producing lateral roots [ 2 3 ]. It was found that an increase in tiller number or shoot dry weight enhanced the root density or root biomass, respectively [ 4 5 ]. Interestingly, such root-shoot relationship exists in the vegetative phase but not in the reproductive phase [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These tillers produce nodal (adventitious) roots which penetrate easily in soil along with seminal roots and establish a network of extensive roots by producing lateral roots [ 2 3 ]. It was found that an increase in tiller number or shoot dry weight enhanced the root density or root biomass, respectively [ 4 5 ]. Interestingly, such root-shoot relationship exists in the vegetative phase but not in the reproductive phase [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These opposite root phenotypes were caused by expression level of the OsNAC6 in roots of nac6 mutants and OsNAC6 overexpressors (Figure m). As root number positively correlates with tiller number (Hockett, ), we evaluated the average root number per tiller, which was found to be similar among all the genotypes (Figure n). We therefore concluded that the root number variation was caused by OsNAC6 overexpression and the nac6 mutation leads to abnormal tiller development.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in sorghum, the ortholog of TB1 ( SbTB1 ) was shown to be involved in the shade-dependent decline in tillering [ 39 ], a stress which decreases crown root number in maize [ 36 , 37 ]. In other cereals, Green Revolution breeding for dwarfism increased both tiller number and crown root number in wheat, barley and rice [ 40 - 43 ]. A single locus ( ari.e.…”
Section: Discussionmentioning
confidence: 99%